Ordering and diffusion in liquid magnesium antimonide (Mg3Sb2) from hypernetted-chain theory and molecular dynamics simulation - Akdere, Unsal; Gunay, Seckin D.; Tasseven, Cetin (SPRINGER HEIDELBERG, 2019)
The static structure and ionic transport in molten Mg3Sb2 was investigated by means of the hypernetted-chain theory of liquids (HNC) and the molecular dynamics simulation (MD) using a semi-empirical pairwise potential together with the liquid-state density that was estimated from the procedure of finding minimum energy. Magnesium sublattice melts into a more disordered liquid state with a higher mobility compared to antimony. Highly mobile magnesium ions indicate the cluster distribution over a range. Tendency of the pre-peak at low k region (k1.7 angstrom(-1)) in the pair structure factor S-NN(k) may be the result of the one of the n-fold Voronoi coordination polyhedral clusters that dominates over the other clusters. The results also suggest that the pair structure factor of the less mobile ion influences the low-k peak in S-NN(k) that might be a characteristic feature of the systems whose components have markedly different self-ionic diffusion.
Keywords: Liquid; Magnesium antimonide; Structure; Diffusion; PROGRAM; Chemistry; Electrochemistry; Physics